A study of the validity and the reliability of the Geriatric Anxiety Inventory in screening for anxiety after stroke in older inpatients - Kneebone, Ian I.; Fife-Schaw, Chris; Lincoln, Nadina; Harder, Helena (SAGE, 2016)
Objectives: To investigate the validity and reliability of the Geriatric Anxiety Inventory in screening for anxiety in older inpatients post-stroke.